Synthesis, Characterization and Antioxidant Properties of a New Lipophilic Derivative of Edaravone - Cristina Minnelli; Emiliano Laudadio; Roberta Galeazzi; Dario Rusciano; Tatiana Armeni; Pierluigi Stipa; Mattia Cantarini; Giovanna Mobbili (MDPI AG, 2019)
As part of a program aimed to obtain antioxidants able to interact with cell membrane, edaravone (EdV, 3-methyl-1-phenyl-2-pyrazolin-5-one), a well-known free radical scavenger, has been modified by alkylation at its allylic position (4) with a C-18 hydrocarbon chain, and the increased lipophilicity has been determined towards the interaction with liposomes. The obtained derivative has been studied by means of density functional theory (DFT) methods in order to characterize its lowest energy conformers and predict its antioxidant properties with respect to the parent compound EdV. The in vitro antioxidant activity of C18-edaravone was studied by means of the α,α-diphenyl-β-picrylhydrazyl (DPPH) assay and in lipid peroxidation experiments performed on artificial lipid membranes using water-soluble as well as lipid-soluble radical initiators. Moreover, since oxidative stress is involved in numerous retinal degenerative diseases, the ability of C18-edaravone to contrast 2,2-azobis (2-amidinopropane hydrochloride) (AAPH)-induced cell death was assessed in adult retinal pigmented epithelium (ARPE-19) cells. Overall, the results demonstrated that the newly synthesized molecule has a high affinity for lipid membrane, increasing the efficacy of the unmodified edaravone under stress conditions.